Enhancing Early Prayer Discipline: Student-Teacher Collaboration Impact - NISAK, NUR MASLIKHATUN; Asmaul, Husna (Universitas Muhammadiyah Sidoarjo, 2024)
This qualitative study investigates the challenges and strategies in fostering congregational prayer discipline among grade III students at Muhammadiyah 1 Sedati Elementary School Mosque. Utilizing interviews, observation, and documentation, the research explores obstacles such as disorder, limited understanding, and distractions during midday prayers. Collaborative efforts between teachers and prayer enforcers from higher grades were found effective in overcoming these challenges, enhancing students' discipline during prayers. The study underscores the significance of teacher guidance and collaborative initiatives between schools and mosques in shaping students' character and spirituality from an early age. Highlight: Early spiritual development: Shaping discipline in congregational prayer fosters character in young students. Teacher-student collaboration: Overcoming challenges enhances prayer discipline. School-mosque integration: Encourages active participation in congregational prayers. Keywoard: Congregational prayer, Discipline, Elementary school, Collaboration, Character development